Self-expanding metal stents for the palliation of malignant gastric outlet obstruction in patients with peritoneal carcinomatosis - Rademacher, Christoph; Jakobs, Ralf (World journal of gastroenterology, 2016)
Self-expanding metal stents for the palliation of malignant gastric outlet obstruction in patients with peritoneal carcinomatosis
Gesehen am 04.12.2019